2021
DOI: 10.1093/advances/nmab002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid or Base Interventions on Bone Health: A Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: Osteoporosis is a global health issue among the aging population. The effect of the acid or base interventions on bone health remains controversial. This study performed a systematic review and meta-analysis to investigate effects of acidic diets and alkaline supplements on bone health simultaneously. We conducted a comprehensive literature search in 5 available databases and 1 registered clinical trial system to identify randomized controlled trials (RCTs) that assessed effects of the acid-base intervention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
4
0
4
Order By: Relevance
“…Consumption of plant protein sources typically result in a more bone‐sparing alkaline metabolic environment, which may increase BMD. 32 In addition, animal foods have typically a higher sodium chloride (NaCl) content, 33 and a high NaCl intake combined with a low calcium intake causes high calcium excretion, leading to bone resorption. 34 Previous cross‐sectional research in older adults also found positive associations between animal protein 5 , 35 , 36 and plant protein 5 , 35 with total body and spine BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of plant protein sources typically result in a more bone‐sparing alkaline metabolic environment, which may increase BMD. 32 In addition, animal foods have typically a higher sodium chloride (NaCl) content, 33 and a high NaCl intake combined with a low calcium intake causes high calcium excretion, leading to bone resorption. 34 Previous cross‐sectional research in older adults also found positive associations between animal protein 5 , 35 , 36 and plant protein 5 , 35 with total body and spine BMD.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also reasons to argue that plant protein would lead to increased BMD. Consumption of plant protein sources typically result in a more bone‐sparing alkaline metabolic environment, which may increase BMD 32 . In addition, animal foods have typically a higher sodium chloride (NaCl) content, 33 and a high NaCl intake combined with a low calcium intake causes high calcium excretion, leading to bone resorption 34 .…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did not conduct any further statistical analysis but only applied the Hill standard review to retrospectively describe the relationship between acid load and bone metabolism. In an additional meta-analysis of 13 randomized clinical trials, alkaline supplementation had beneficial effects on bone metabolism and acidic diets were not harmful for bone health (44). Several randomized controlled trials have reported that high-protein diets which are considered acid-producing diets, have no significant effect on bone turnover markers and BMD (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…B. um 50 mEq/Tag, so werden rund 70 mg Calcium weniger ausgeschieden [137]. Dieser Zusammenhang zwischen verminderter Säurelast und reduzierter Calciumexkretion wurde auch für alkalische Wässer [136,138] und Basensupplemente auf Basis von Kaliumcitrat oder -bikarbonat beschrieben [139] (siehe ▶Abb. 4).…”
Section: Calciumausscheidungunclassified